Viscosity-Sensitive Dyes And Method - Shkand, T.V.; Чиж, М.О.; Sleta, I.V.; Tatarets, A.L.; Roshal, O.D.; Patsenker, L.D.; Sandomyrskiy, B.P.; Terpetschnig, E.A. (IPC8 Class: AG01N3358FI USPC Class: 436 94 Publication date: 2016-03-31 Patent application number: 20160091495, 2016)
Viscosity-Sensitive Dyes And Method
Shkand T.V., Chyzh M.O.,Sleta I.V., Tatarets A.L., Roshal O.D., Patsenker L.D., Sandomyrskiy B.P., Terpetschnig E.A. Viscosity-Sensitive Dyes And Method. IPC8 Class: AG01N3358FI USPC Class: 436 94 Publication date: 2016-03-31 Patent application number: 20160091495
Keywords: Viscosity-Sensitive Dyes